Investigating the Impacts of Nitrogen Doses and Rhizobacteria on Sugar Beet (Beta vulgaris L.) Yield and Quality Parameters for Sustainable Cultivation - SUSAR, Ali; ŞATANA, Aziz (ISPEC Tarım Bilimleri Dergisi, 2024)
Rising costs and environmental concerns associated with chemical fertilizers in modern agriculture necessitate exploring sustainable alternatives. Plant growth-promoting soil bacteria offer a promising solution. This study evaluated the impact of nitrogen-fixing rhizobacteria (Bacillus subtilis, Bacillus megaterium, Lactococcus spp., Azospirillum, Rhizobium, Acetobacter, and Azotobacter) on the yield and quality traits of sugar beet (Beta vulgaris L.) under different nitrogen application rates, both with and without chemical nitrogen application. Our findings suggest that co-inoculation with rhizobacteria can significantly enhance sugar beet yield. Under chemical nitrogen application, the B₁ + N₃ treatment achieved the highest storage beet yield (7713 kg da ⁻¹) and sugar yield (1444.00 kg da ⁻¹). In the absence of chemical nitrogen application, the B₂ + N₀ treatment showed promising results (5047 kg da ⁻¹ beet yield, 985.40 kg da ⁻¹ sugar yield). The study demonstrates the significant potential of bacterial applications for promoting growth and improving the agronomic traits of sugar beet, offering a sustainable and organic agricultural alternative.